Potential Pathological Effects Induced by Inhaled Atmospheric Nanoparticles - Ozdan Akram Ghareeb; Qahtan Adnan Ali (Disease and Health Research: New Insights Vol. 11, 2024)
The atmosphere is a vast reservoir whose composition is constantly changing through human activities, and these changes can have significant health and environmental consequences. Air pollution is one of the most important environmental problems that poses a constant threat to the health and quality of life of residents. Nanoparticles (NPs) are of interest to researchers worldwide due to their potential to induce toxicity in vital organs of the body. This study reviews the potential pathological effects of inhaled atmospheric nanoparticles on the body, to contribute to a relatively adequate archive of exposure to nanoparticles in the atmosphere and their negative effects on health. There is an urgent need to clarify this to contribute to controlling human exposure to nanoparticles at toxic doses. These particles are considered one of the most important air pollutants because they remain suspended in the atmosphere for a long time and thus can travel over wide distances due to their extremely small size. These particles can cause pathological disorders in the respiratory, cardiovascular and nervous systems. It was concluded that nanoparticles can effectively reach the bloodstream and cell membrane barriers, settle in organs and tissues, and even penetrate the blood-brain barrier and reach the brain. The study recommends conducting more accurate and detailed studies.